Transcriptomic analysis identifies key genes associated with nutrient deprivation responses in infectious bursal disease virus infection - Jiaxing Wang; Qiangzhou Wang; Yuyu Ping; Xuan Huang; Ting Yang; Zongping Liu; Hao Bai; Guobin Chang; Shihao Chen (BMC Genomics)
Abstract Infectious bursal disease virus (IBDV) causes a highly contagious and immunosuppressive disease that severely impacts the poultry industry. However, the molecular basis of IBDV-induced immunosuppression remains poorly understood. In this study, we investigate key genes implicated in this process, focusing on the interplay between metabolism and immune regulation. IBDV infection enhanced glucose and glutamine uptake in HD11 cells. Transcriptome analysis across glucose-starved, amino acid-starved, IBDV-infected, and control groups identified key differentially expressed genes (DEGs) linked to immune and metabolic pathways. Specifically, 612 DEGs were associated with glucose starvation, 998 with amino acid starvation, and 496 shared between both conditions. Enrichment analysis revealed involvement in cytokine signalling, amino acid biosynthesis, and antiviral responses. qPCR validated ENO2 and MAT1A expression changes, and a regulatory network analysis highlighted their potential roles in nutrient stress and IBDV pathogenesis. This study presents a novel strategy to identify genes involved in nutrient deprivation during IBDV infection, highlighting ENO2 and MAT1A as key contributors to immune cell dysfunction.